Is it possible to alter the embryo lipid accumulation with reduction of fetal bovine serum and use ofl-carnitine forin vitromaturation of bubaline oocytes? - Figueiro, Marivaldo Rodrigues [UNESP]; Garcia, Joaquim Mansano [UNESP]; Lima, Marina Ragagnin de [UNESP]; del Collado, Maite; Saraiva, Naiara Zoccal (Cambridge Univ Press, 2020)
In vitroembryo production (IVEP) is a procedure that can promote genetic improvement in a short time frame. However, the success rates obtained with this biotechnology in water buffaloes are still inconsistent, and can be associated with the high concentration of lipids in the cytoplasm of oocytes and embryos. The objective of this study was to evaluate the effects of reduced concentration of fetal bovine serum (FBS) and/or use ofl-carnitine duringin vitromaturation (IVM) on the preimplantation development and lipid accumulation in bubaline embryos. In a first experiment, the lowest concentration of FBS in the IVM medium (0%, 2.5%, 5% or 10%) was determined, and the lowest concentration that maintained good embryo development rates was 5%. In a second experiment, the addition of 5 mM ofl-carnitine into the maturation medium was evaluated. The blastocysts produced were submitted to lipid evaluation involving staining followed by observation using optical (Oil Red O) and confocal (BODIPY 493/503) microscopy. No difference was observed between the 5% and 10% FBS groups, which were superior to the 0% and 2.5% groups. Furthermore, the performance of the groups treated with 5% and 10% FBS was better than the groups supplemented withl-carnitine. There was no difference regarding embryo lipid accumulation. The results indicated that it is possible to reduce the FBS concentration to 5% inin vitromaturation medium for production of bubaline embryos, and supplementation with 5 mMl-carnitine does not increase embryo production.
Keywords: Buffaloes; Embryo development; Fetal bovine serum; Lipid metabolism modulator; Neutral lipids